Bid Participates in Genotoxic Drug-Induced Apoptosis of HeLa Cells and Is Essential for Death Receptor Ligands' Apoptotic and Synergistic Effects - Köhler, Barbara (Public Library of Science, 2008)
BACKGROUND: The BH3-only protein Bid is an important component of death receptor-mediated caspase activation. Bid is cleaved by caspase-8 or -10 into t-Bid, which translocates to mitochondria and triggers the release of caspase-activating factors. Bid has also been reported to be cleaved by other proteases. METHODOLOGY/PRINCIPAL FINDINGS: To test the hypothesis that Bid is a central mediator of stress-induced apoptosis, we investigated the effects of a small molecule Bid inhibitor on stress-induced apoptosis, and generated HeLa cells deficient for Bid. Stable knockdown of bid lead to a pronounced resistance to Fas/CD95- and TRAIL-induced caspase activation and apoptosis, and significantly increased clonogenic survival. While Bid-deficient cells were equally sensitive to ER stress-induced apoptosis, they showed moderate, but significantly reduced levels of apoptosis, as well as increased clonogenic survival in response to the genotoxic drugs Etoposide, Oxaliplatin, and Doxorubicin. Similar effects were observed using the Bid inhibitor BI6C9. Interestingly, Bid-deficient cells were dramatically protected from apoptosis when subtoxic concentrations of ER stressors, Etoposide or Oxaliplatin were combined with subtoxic TRAIL concentrations. CONCLUSIONS/SIGNIFICANCE: Our data demonstrate that Bid is central for death receptor-induced cell death and participates in anti-cancer drug-induced apoptosis in human cervical cancer HeLa cells. They also show that the synergistic effects of TRAIL in combination with either ER stressors or genotoxic anti-cancer drugs are nearly exclusively mediated via an increased activation of Bid-induced apoptosis signalling.